Role of Clostridium perfringens toxins in necrotic enteritis in poultry - Ramírez, M (2016)
Poultry products represent over 30% of animal protein consumption worldwide, and its demand is growing considerably. The current global annual production of poultry meat and eggs is more than 115 million tons and 70 million tons, respectively. Necrotic enteritis (NE) in poultry is a reemerging infectious disease caused by certain strains of Clostridium perfringens. This bacterium is found in limited quantities as a normal inhabitant of the birds’ gut; however, under certain circumstances, a pathogenic strain proliferates and secretes a variety of bacteriocins, mucins, and adhesins that favors bacteria colonization and establishment. Once bacterial population reaches a certain density, toxin production is triggered which induces mucosal damage. NE generates a dramatic reduction of production levels and a significant increase in mortality in flocks of broilers and laying hens, leading to annual economic losses for the poultry industry estimated to be over $6 billion. NE may manifest as an acute or chronic enterotoxemia. Acute infection is associated with higher rates of mortality and chronic infection, with loss of weight and productivity in sick animals. There is evidence that immunization with formalin-inactivated crude supernatants, native or modified toxins, or other proteins induces partial protection against NE. This review summarizes the findings concerning virulence factors associated with NE pathogenesis and the efforts oriented to develop rational strategies to prevent and control this disease